PROTEUS SYNDROME: NEED FOR PATIENT CENTRIC THERAPY - Kuppusamy, Gowthamarajan; Radhakrishnan, Arun; K Shanmukhan, Nikhitha; M, Prineethaa; S, Anusha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Proteus syndrome (PS) is a hamartomatous disorder with multisystem involvement that results from mutation in the AKT1gene. Since the symptoms and severity of PS are unique to each patient, diagnosis and treatment become hard for the physician. This article is concentrated upon the identification and recognition of specific characteristics of the disease, pathophysiology, symptoms, diagnosis, treatment and the necessity of advanced diagnosis, effective generalized and personalized therapy, as well as the requirement of new drugs for the management of PS. Detailed studies on the PS and evidence from the case reports revealed the requirement of intensive care, accurate diagnosis, and an effective treatment for each patient preferably patient-centric drug delivery due to the high degree of variation in the symptoms and clinical features among patients.